The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1186/s13569-016-0052-4
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of care for patients with advanced soft tissue sarcoma: experience from Australian sarcoma services

Abstract: BackgroundThere is a paucity of data on the current management of patients with advanced soft tissue sarcoma (STS) in the Australian health care setting. This study utilised the Australian sarcoma database to evaluate the patterns of care delivered to patients with advanced STS at Australian sarcoma services.MethodsProspectively collected data from six sarcoma centres in Australia were sourced to identify patients diagnosed with advanced STS between 1 January 2010 and 31 December 2012. Descriptive statistics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 20 publications
4
9
0
Order By: Relevance
“…Anthracycline-based chemotherapy is recommended as a standard-of-care in palliative settings in well-known guidelines such as the National Comprehensive Cancer Network (NCCN) and the European Society of Medical Oncology (ESMO). In this study, anthracycline-based chemotherapy was the most frequent treatment for advanced STS (50%), which is consistent with previous studies from other countries such as Germany, the United Kingdom and Australia [26-28]. However, when analyzed by specific regimen, doxorubicin plus ifosfamide (AI) combination therapy was the most frequently used, whereas doxorubicin monotherapy was most frequently used in Germany, the United Kingdom, and Australia [26-28].…”
Section: Discussionsupporting
confidence: 89%
“…Anthracycline-based chemotherapy is recommended as a standard-of-care in palliative settings in well-known guidelines such as the National Comprehensive Cancer Network (NCCN) and the European Society of Medical Oncology (ESMO). In this study, anthracycline-based chemotherapy was the most frequent treatment for advanced STS (50%), which is consistent with previous studies from other countries such as Germany, the United Kingdom and Australia [26-28]. However, when analyzed by specific regimen, doxorubicin plus ifosfamide (AI) combination therapy was the most frequently used, whereas doxorubicin monotherapy was most frequently used in Germany, the United Kingdom, and Australia [26-28].…”
Section: Discussionsupporting
confidence: 89%
“…The addition of olaratumab to first line therapy is likely to solidify the use of doxorubicin in the first line [ 17 ]. Prior studies of first-line treatment have found that the most common regimens were doxorubicin monotherapy (34%) or an anthracycline + ifosfamide (30%) [ 11 ], anthracycline-based (44%) or gemcitabine-based (28%) [ 13 ], doxorubicin (± ifosfamide) (46%) [ 12 ], or doxorubicin (± ifosfamide) (66%) [ 18 ]. Docetaxel + gemcitabine may be preferred for certain mSTS including leiomyosarcomas and undifferentiated pleomorphic sarcomas (UPS) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest widespread use of gemcitabine in LOT2 prior to pazopanib’s US availability, either alone or in combination with docetaxel, and less variation in LOT2 regimen preference across different study populations. In contrast, Bae and colleagues found that 53% used ifosfamide in LOT2 in an Australian advanced STS population, although pazopanib was sporadically used as subsequent LOTin Bae’s study population following its availability in Australia in March of 2014 [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, many patients develop severe symptoms like pain or local complications due to uncontrolled progressions of localized lesions, which are generally amenable to palliative RT. According to a recent survey from Australia, 37% of locally advanced or metastatic STS patients received palliative RT during their course of disease [97], mainly to symptomatic lesions of bone and lung or mediastinum. Although this comprises a substantial number of patients, the literature regarding efficacy, side effects, and optimal dose and fractionation schedules specifically for STS patients is very scarce.…”
Section: Palliative Rtmentioning
confidence: 99%